Conceptual principles of the wounded combatants’ evacuation, suffering military surgical trauma on the medical support levels - I. P. Khomenko; I. A. Lurin; S. O. Korol; V. Yu. Shapovalov; B. V. Matviichuk (Клінічна хірургія)
Objective. To improve the results of treatment of the wounded persons, suffering a combat surgical trauma, elaborating and introducing of objective scales of the trauma severity estimation into the medical evacuation system while conduction of Antiterroristic operation / Operation of Joint Forces.